2020
DOI: 10.1002/app.50221
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber‐carbon black coagulation: Following the nanostructure evolution from a colloidal suspension to a composite

Abstract: Making elastomeric composite materials via heteroaggregation of a binary colloidal suspension of Natural Rubber (NR) latex and Carbon Black (CB) filler is an interesting production method to obtain an efficient dispersion in the polymer matrix. This study successfully employs an original approach of field emission scanning electron microscopy (FESEM) to investigate for the first time the nanostructure evolution of a coagulum originated from the aggregation of NR globules with CB filler in suspension. More spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For the latter, it was recently reported that when CB aggregates are in contact with NR globules, coalescence of the latter was promoted. 27 3.2. NR−SiO 2 NPs Heteroaggregates: Structural Evolution during Drying and Shearing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the latter, it was recently reported that when CB aggregates are in contact with NR globules, coalescence of the latter was promoted. 27 3.2. NR−SiO 2 NPs Heteroaggregates: Structural Evolution during Drying and Shearing.…”
Section: Resultsmentioning
confidence: 99%
“…The sample preparation and description of the shearing module used in these experiments were described in detail elsewhere. 27 Briefly, the SiO 2 NPs binary colloidal suspension was placed between two microscopy coverslips (with a controlled gap width of 500 μm) well suited for the application of controlled shear. This was obtained using a commercial device called RheOptiCAD (CAD instrument).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This solution was again sonicated for better dispersion of the additives, with a 600 W probe ultrasound for 25 min in an ice bath. The suspension formed was poured into Petri dishes in volumes of 50 ml to produce films in a casting-like process [48,49]. The plates were then placed in an oven with air circulation at 50 • C and left for 48 h for drying and rubber maturation.…”
Section: Processingmentioning
confidence: 99%